Development of a Topical Emulgel Containing Tulsi and Neem Oils: A Novel Approach for Acne Management - Sahu, Jyoti; Joseph, Jisha; Parab, Vipul Alias; Rai, Neeta; Lunkad, Amit; Bhore, Pritam; Deshpande, Kirti; Kale, Pallavi; Sah, Ravi Kumar; Baldota, Jayesh (International Journal of Pharmaceutical Investigation, 2026)
Objectives This research focused on formulating and assessing a silica-based herbal emulgel enriched with antimicrobial and anti-inflammatory agents, including tulsi (Ocimum sanctum) and neem (Azadirachta indica) oils, to manage acne vulgaris. Materials and Methods A silica-based emulgel was synthesized using carbopol as the gelling agent, with tulsi and neem oils as key bioactive components. Tween 80 and Span 20 were incorporated as emulsifiers to stabilize the formulation. Four batches (F1-F4) were developed with varying ingredient concentrations and analyzed for consistency, spreadability, pH, viscosity, and washability. Results Among the tested formulations, Batch F4 emerged as the most optimized, demonstrating a smooth texture, high spreadability, non-greasy characteristics, and excellent washability. Silica gel plays a crucial role in enhancing the structural stability and penetration of the formulation into the skin. Tulsi and neem oils exhibited significant antimicrobial and anti-inflammatory activities. The formulation Batch F4 showed optimal results with a pH of 5.0±0.2, spreadability of 13.6 g cm/s, and viscosity of 0.0171 Pa s. The formulation exhibited a non-greasy, smooth texture with excellent washability. The bioactive eugenol in Tulsi and nimbidin in Neem contributed to the observed benefits. Conclusion The developed silica-based herbal emulgel demonstrated significant potential as an effective and user-friendly topical treatment for acne vulgaris. The integration of herbal bioactives with advanced drug-delivery technology presents a promising approach. Further research is warranted to establish clinical efficacy and explore its applications in skincare formulations.
Keywords: Silica-based emulgel; Acne vulgaris; Tulsi and neem oils; Antimicrobial and anti-inflammatory; Dermatological safety